P-207 A survey of radiation exposure among non-destructive testing technicians in Taiwan. (14th March 2023) - Shih, Ping; Chu, Po-Ching; Lin, Chiu-Miao; Yeh, Ching-Tsung; Lin, Ming-Yu
Abstract : Introduction: Five workers engaged in non-destructive testing (NDT) were diagnosed with leukemia and visited the Occupational Injury and Disease Prevention Center for the help of assessment for occupational disease in Taiwan during 2018 and 2019. NDT belongs to industrial radiography in the classification of radiation work, and the purpose of this study is to investigate the ionizing radiation exposure among workers in the industry. Method: Using the National Radiation Workers Dose Database of the Atomic Energy Commission of Taiwan Executive Yuan from 2000 to 2019 to analyze the values of the ionizing radiation badges among the industrial radiography group and other groups exposed to ionizing radiation over these years. The cumulative personal measurement was also analyzed using the characteristics of the longitudinal databases. Results: During this period, workers with dose values greater than the lowest measurable value accounted for 13.29% of the total population potentially exposed to radiation at work, compared to 26.57% of workers in industrial radiography. We also found that the mean annual median dose value for all workers possibly exposes to ionizing radiation was 0.43 mSv and in industrial radiography it was 1.21 mSv. Since 2005, most of the practitioners in the industrial radiography industry have an annual cumulative exposure of more than 20mSv. Moreover, the average personal 20-year cumulative measurement is 7.82 mSv for all ionizing radiation workers and 29.26 mSv among workers engaged in industrial radiography. Conclusion: Industrial radiography workers may have higher exposure to ionizing radiation. This is important to prevent ionizing radiation-related occupational diseases in industrial radiography or NDT workers.